2014
DOI: 10.1038/bmt.2013.214
|View full text |Cite
|
Sign up to set email alerts
|

Results of a randomized trial comparing high-dose chemotherapy plus Auto-SCT and R-FC in CLL at diagnosis

Abstract: The importance of early therapy intensification in B-cell CLL (B-CLL) patients remains to be defined. Even though several studies have been published, no randomized trials comparing directly autologous stem cell transplant (ASCT) and the accepted conventional therapy (that is, rituximab, fludarabine and CY; R-FC) have been reported so far. To assess the benefit of a first-line aggressive therapy, we designed a multicenter, randomized, phase 3 trial comparing R-FC and high-dose chemotherapy supported by ASCT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…21 This benefit is possibly explained by the fact that mini-CHOP and, subsequently, fludarabine monotherapy, as prescribed, were suboptimal therapies in CLL, hence patients randomized to the observation arm were at an inherent disadvantage when compared with those who received HDT/auto-HCT and benefited from the consolidation. 21 This argument is supported by findings from Magni et al 20 who showed that HDT/auto-HCT failed to show improvement in responses, PFS and OS when compared with a contemporary chemoimmunotherapy regimen, consisting of fludarabine, cyclophosphamide and rituximab. Interestingly, the European intergroup randomized trial comparing autografting with observation demonstrated a benefit in lowering risk of relapse as well as improved EFS in the HDT/auto-HCT arm despite the fact that 73% of the subjects in the transplant arm did not receive rituximab as part of the initial regimen.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…21 This benefit is possibly explained by the fact that mini-CHOP and, subsequently, fludarabine monotherapy, as prescribed, were suboptimal therapies in CLL, hence patients randomized to the observation arm were at an inherent disadvantage when compared with those who received HDT/auto-HCT and benefited from the consolidation. 21 This argument is supported by findings from Magni et al 20 who showed that HDT/auto-HCT failed to show improvement in responses, PFS and OS when compared with a contemporary chemoimmunotherapy regimen, consisting of fludarabine, cyclophosphamide and rituximab. Interestingly, the European intergroup randomized trial comparing autografting with observation demonstrated a benefit in lowering risk of relapse as well as improved EFS in the HDT/auto-HCT arm despite the fact that 73% of the subjects in the transplant arm did not receive rituximab as part of the initial regimen.…”
Section: Discussionsupporting
confidence: 71%
“…Brion et al 19 reported two deaths attributed to secondary AML in 39 subjects who were treated with HDT-auto-HCT. None of the subjects who received HDT/auto-HCT in the study by Magni et al 20 were reported to have developed AML/ MDS; it is possible this could be explained by a relatively short follow-up. The relatively low incidence of secondary AML/MDS from these studies 19-21 compared with 9-12% incidence reported in a previous systematic review by our group 10 is probably explained by the fact that the latter patients were offered HDT/ auto-HCT in the relapsed disease setting, suggesting an increased risk of leukemogenesis as a result of cumulative exposure to multiple lines of chemotherapy in this pre-treated group in addition to using TBI as part of the preparative regimen; and/or perhaps by a smaller rate of events in the present analysis (eight AML/MDS cases in 274 autografted patients), possibly related to a relatively short follow-up as previously stated.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Autologous transplantation of stem cells does not offer substantial advantages when compared against new pharmacological treatment On the contrary, allogeneic transplantation is still to be considered for refractory diseases de novo, given the long-term efficacy of new drugs remains unknown [26,27].…”
Section: Introductionmentioning
confidence: 99%